Kualitas Soal Ujian Akhir Berstandar Nasional Mata Pelajaran Bahasa Arab Di MDTA - Nurbaitillah, Siti; Al Farisi, Mohammad Zaka; Maulani, Hikmah (Fakultas Tarbiyah Institut Agama Islam Bani Fattah Jombang, 2024)
This research aims to evaluate the quality of Arabic language examination questions in the National Standardized Final Examination (Ujian Akhir Berstandar Nasional - UABN) at the Nurul Amal Madrasah Diniyah Takmiliyah Awaliyah (MDTA), Karawang, for the academic year 2022/2023. The evaluation involves aspects of validity, reliability, difficulty level, item discrimination, distractor effectiveness, and Bloom's Taxonomy cognitive level. The research method employs a quantitative approach with an ex post facto design. Data were obtained from the documentation of examination questions and answer sheets, as well as interviews with teachers and students. The participants comprised 14 fourth-grade students of MDTA, selected using a saturated sampling technique. Analysis was conducted using Microsoft Office Excel for validity and reliability, and Anbuso Ver.8 software for difficulty level, item discrimination, and distractor effectiveness. The validity analysis results showed that only 20% of the items were valid, highlighting the need for structural improvements in item formulation. The test reliability met the desired standard, with 8 valid items yielding higher reliability. The difficulty level exhibited variation, ranging from difficult to easy. Evaluation of students' and teachers' perceptions revealed differences in assessing the difficulty level of the questions. Item discrimination analysis identified items with good discrimination, but some were inadequate. The effectiveness of distractors in 67.5% of the items required revision due to unsatisfactory performance. This study contributes to understanding the quality of Arabic language examination questions at MDTA and offers improvement suggestions. HOTS and LOTS) indicate that 21 questions fall under the LOTS category, while 19 other questions fall under the HOTS category. The findings are expected to positively influence the development of Arabic language learning evaluations, especially at MDTA